Effects, Damage Characteristics and Recovery Potential of Traffic‐induced Nitric Oxide Emissions in PEM Fuel Cells under Variable Operating Conditions1. Issue 5 (27th September 2018) - Misz, U.; Talke, A.; Heinzel, A.; Beckhaus, P.
Abstract: Understanding of the influence of traffic‐related nitrogen oxides on proton exchange membrane (PEM) fuel cells is essential to improve life time and durability of fuel cell vehicles. In a 3‐year work, both the damaging mechanisms and the influence of NOx on PEM fuel cells under real environmental and operating conditions became more comprehensible. It could be shown that even a low concentration level of 150 ppb NOx, which is often exceeded in traffic areas, causes considerable power losses. Furthermore, NO leads to significantly faster voltage drops compared to NO2, so typical NO peaks during rush hour traffic can reduce the fuel cell power. The concentration profile also has an influence on the degradation. The impact of NOx peaks is more negative compared to continuous NOx dosing when charging the fuel cell with the same total amount of NOx . It is possible to recover the fuel cell but it takes several hours depending on operating conditions and prior contamination level. To increase the recovery process the fuel cell has to be operated at a cathode potential below 0.3 V to reduce NOx and detach the contaminant from the platinum catalyst. A negative effect is the formation of NH4 +, which is suspected to decompose the membrane in long term perspective.